THE ROLE OF STAFF DEVELOPMENT IN ORGANISATIONS - SHONHIWA, DOCTOR CAXTON (IJRDO- Journal of Educational Research, 2017)
This paper offers suggestions and tools for employees and their supervisors to help employees achieve greater success in their current position and plan for career advancement. The paper argues that a skilled and knowledgeable workforce positively impacts organisational performance. Employee development should be a shared responsibility which requires collaboration between the employee and supervisor. The supervisor’s role as a performance coach includes such activities as clarifying performance and behavioural expectations, helping employees understand the organization as a whole, helping employees understand the organisations’ long and short-term goals, identifying learning opportunities, giving positive and concrete feedback and providing necessary resources. In addition to meeting current performance expectations, employees must be able to adapt to meet evolving organisational needs. For example, new skills and knowledge are often required to keep pace with technological change and new departmental procedures. The attainment of knowledge, skills and abilities can be achieved in numerous ways; many at no or low cost within the organisation.